2020
DOI: 10.48550/arxiv.2001.08041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loci of 3-periodics in an Elliptic Billiard: why so many ellipses?

Abstract: We analyze the family of 3-periodic (triangular) trajectories in an Elliptic Billiard. Specifically, the loci of their Triangle Centers such as the Incenter, Barycenter, etc. Many points have ellipses as loci, but some are also quartics, self-intersecting curves of higher degree, and even a stationary point. Elegant proofs have surfaced for locus ellipticity of a few classic centers, however these are based on laborious case-bycase analysis. Here we present two rigorous methods to detect when any given Center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We can roughly divide it into three groups: (i) the study of point loci over certain triangle families [18,19,27], (ii) proving that loci of certain Poncelet triangle families are of a given curve type [9,13,21,23], and (iii) proving properties and invariants over N ≥ 3 Poncelet families [2,4,6,22]. Also related is the Steiner-Soddy Poncelet family which are the polar image of the so-called Brocard porism with respect to the circumcircle [10].…”
Section: Related Workmentioning
confidence: 99%
“…We can roughly divide it into three groups: (i) the study of point loci over certain triangle families [18,19,27], (ii) proving that loci of certain Poncelet triangle families are of a given curve type [9,13,21,23], and (iii) proving properties and invariants over N ≥ 3 Poncelet families [2,4,6,22]. Also related is the Steiner-Soddy Poncelet family which are the polar image of the so-called Brocard porism with respect to the circumcircle [10].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, over said family, the locus of both X 3 and X 5 are concentric, axisaligned ellipses with semi-axes are given by [10]:…”
Section: Concentric Axis-aligned: Invariant Power Of Originmentioning
confidence: 99%
“…In [10] it was shown that over confocal 3-periodics, 29 triangle centers (out of the first 100 in [13]) trace out ellipses. Explicit expressions are given for the semi-axes of each locus.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the confocal family, loci of both incenter and excenters 1 are ellipses with reciprocal aspect ratios [7,19]. Loci of other notable centers such as the circumcenter, orthocenter, etc., are also elliptic [7,6,10]. Certain loci are non-conic (e.g., the symmedian point, the Fermat point, etc.)…”
Section: Related Workmentioning
confidence: 99%